The Effect of Nurses' SBAR Communication Technique Training on the Application of Weighing in Inpatient Facilities - Julianti, Riya; Habibi, Alpan (CV Media Inti Teknologi, 2026)
Study background : Effective communication between nurses, especially in the handover process, is an important element in ensuring patient safety and the quality of nursing services. One of the structured communication methods that has proven effective is SBAR (Situation, Background, Assessment, Recommendation) communication. However, the implementation of SBAR in various hospitals in Indonesia is still not optimal, mainly due to the lack of adequate training for nurses.Aim : to analyze the effect of nurses' SBAR communication technique training on the application in handover in inpatient settings.Methods : This study used a literature review method with a structured search strategy based on the PICO/T framework.Results : The characteristics of nurses who participated in the training were generally 20–30 years old, female, with a D3 or S1 educational background, and had a working period of <10 years. Training methods involving theory, discussion, role play simulation, and hands-on coaching have been shown to be effective in improving nurses' handover communication skills. The results of the analysis showed that SBAR training significantly improved the knowledge, skills, and attitudes of nurses in conveying information in a structured, systematic, and clear manner.Conclusion : SBAR communication training is effective in improving the knowledge, skills, and attitudes of nurses when weighing. Obstacles to implementation in the field include workload, old habits, and lack of managerial support.